Psychological Distress in Intracranial Neoplasia: A Comparison of Patients With Benign and Malignant Brain Tumours - Fehrenbach, Michael Karl; Brock, Hannah; Mehnert-Theuerkauf, Anja; Meixensberger, Jürgen (Frontiers in Psychology, 2021)
Objective. We aimed to assess psychological distress in patients with intracranial neoplasia, a group of patients who suffer from severe functional, neurocognitive and neuropsychological side effects, resulting in high emotional distress. Methods. We conducted a cross-sectional study, including inpatients with brain tumours. Eligible patients completed validated self-report questionnaires measuring depression, anxiety, distress, symptoms of posttraumatic stress disorder (PTSD), fear of progression and health-related quality of life. The questionnaire set was completed after brain surgery and receiving diagnosis and before discharge from hospital. Results. A total of n=31 patients participated in this survey. 14 of them suffered from malignant (n=3 metastatic neoplasia) and 17 from benign brain tumours. Mean values of the total sample regarding depression (M=9.28, SD=6.08) and anxiety (M=6.00, SD=4.98) remained below the cut-off≥10. Mean psychosocial distress (M=16.30, SD=11.23, cutoff≥14) and posttraumatic stress (M=35.10, SD=13.29, cutoff≥32) exceeded the clinically relevant cut-off value in all the patients with intracranial tumours. Significantly more patients with malignant (79%) than benign (29%) brain tumours reported posttraumatic stress disorder symptoms (p=.006). Conclusion. Distress and clinically relevant PTSD symptoms in patients with intracranial neoplasia should be routinely screened and treated in psycho-oncological interventions immediately after diagnosis. Especially neuro-oncological patients with malignant brain tumours or metastases need targeted support to reduce their emotional burden.